You Say dientito, I Say dentito: Navigating Complex Word Formation in Second Language Spanish. Issue 3 (21st April 2017) - Carlson, Matthew T.; Gerfen, Chip
Abstract: Native speakers seamlessly marshal morphological resources to create new words, displaying striking consistency even where multiple options are available, as when a stem contains a phonological alternation. This is true even when these options appear to be idiosyncratically applied in existing words. For example, in derived words, the alternation of diphthongs and monophthongs in certain Spanish stems defies traditional morphophonological analysis, but native speakers nonetheless agree on when to use one and when to use the other in novel derivations. Here we ask how second language learners of Spanish cope with this subtlety. Recently, native speakers' agreement has been attributed to the way phonotactic and morpholexical properties influence morphological processing. In a lexical decision experiment, we show that while the polarity of learners' responses differed from earlier native speaker results, their response latencies exhibit striking sensitivity to the very same ingredients shown to predict nativelike behavior. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .